Avtoklav za preiskave korozijskih lastnosti kovin v hladilni vodi lahkovodnega jedrskega reaktorja - Zajec, Bojan (Vakuumist, 2015)
Autoclave is a pressure vessel than enables exposure of specimen to the water or steam at high temperature and pressure. The most common variant of the autoclave encountered in everyday life is a pressure cooker. Current paper presents the operation and characteristics of larger autoclaves running at substantially higher pressure and temperature. They are used for the simulation of the environment in the primary cooling loop of light water nuclear reactors. It is only this environment that enables study of corrosion processes on various types of steels and metals that comprise critical parts of primary loop. Corrosion is the major degradation process in the primary loop hence corrosion knowledge and control is essential for nuclear reactor safety and long-term operation. Current paper deals with all experimental aspects of corrosion studies in simulated primary loop environment and gives detailed overview of autoclave characteristics and operation. Out of several types of localized corrosion the main focus is on the stress corrosion cracking since it is very difficult to detect at early stages. Modern monitoring and analytical techniques that are used for the detection of corrosion andžor cracking processes during the exposure and after it are presented together with several measurement examples.
Keywords: autoclave; avtoklav; corrosion; korozija; lahkovodni jedrski reaktor; light water nuclear reactor; napetostno korozijsko pokanje; primarni hladni krog; primary cooling loop; stress corrosion cracking; superheated water; vroča voda